Serum Uric Acid as a Prognostic Factor of Acute Myocardial Infarction in Hospitalized Patients (TAJ: Journal of Teachers Association, 2021)
Background: Among non-communicable diseases, acute myocardial infarction (AMI) is a common killer of people in the world. The management of AMI patients is one of the major challenges in the field of cardiology. Uric acid has several effects of potential interest in cardiovascular disease. There are some markers indicating an unfavorable prognosis in AMI patients. Uric acid is one of the markers that have been evaluated in research.Objective: The aim of this study was to assess the association between serum uric acid level and in-hospital outcomes of AMI patients.Patients and methods: This longitudinal descriptive study was conducted over 115 AMI patients in the Cardiology Unit of Rajshahi Medical College Hospital during the period of January 2015 to December 2016. Baseline characteristics such as age, sex, BMI, BP, RBS, risk factors (hypertension, DM, smoking, family history of IHD, dyslipidemia), and outcomes of AMI patients (acute LVF, arrhythmia, conduction block, cardiogenic shock, death) were recorded. We measured the serum uric acid of this patient at admission.  Results: The mean age of patients was 52.83±10.71 years. Out of 115 patients, 83.5% were male, and 16.5% were female. Among the risk factors, 65.2% of patients had HTN, 20.9% DM, 64.3% smoking, 16.5% family history of IHD, and 47.8% dyslipidemia. Out of 115, 35.7% of patients demonstrated high serum uric acid. In outcomes of AMI patients, acute LVF 24.4% (p=0.031) and death 12.2% (p=0.041) were significantly higher in patients with high serum uric acid levels.Conclusion: Significant association was found between high serum uric acid level and in-hospital outcomes of AMI patients. So, estimation of serum uric acid may offer an inexpensive, quick, and non-invasive method for identifying such high-risk patients.TAJ 2021; 34: No-1: 26-32